Oxidation Reactions with Bioinspired Mononuclear Non‐Heme Metal–Oxo Complexes. Issue 27 (16th June 2016) - Engelmann, Xenia; Monte‐Pérez, Inés; Ray, Kallol
Abstract: The selective functionalization of strong C−H bonds and the oxidation of water by cheap and nontoxic metals are some of the key targets of chemical research today. It has been proposed that high‐valent iron‐, manganese‐, and copper‐oxo cores are involved as reactive intermediates in important oxidation reactions performed by biological systems, thus making them attractive targets for biomimetic synthetic studies. The generation and characterization of metal–oxo model complexes of iron, manganese, and copper together with detailed reactivity studies can help in understanding how the steric and electronic properties of the metal centers modulate the reactivity of the metalloenzymes. This Review provides a focused overview of the advances in the chemistry of biomimetic high‐valent metal–oxo complexes from the last 5–10 years that can be related to our understanding of biological systems. Abstract : High‐valent Fe‐, Mn‐, and Cu‐oxo cores are proposed as reactive intermediates in biological oxidation reactions. The generation of well‐characterized model compounds can provide vital insights into the mechanisms of such enzymatic reactions. This Review provides a comprehensive summary of recent advances in biomimetic high‐valent metal–oxo complexes related to our understanding of biological systems.